Effect of replacing nitrite with ginger powder in brine solution on the quality of cured beef - E. S. Apata; O. T. Lasisi; O. O. Olaleye; O. C. Apata; J. E. Okolosi; Y. O. Uthman-Akinhanmi; O. Y. Adedeji; M. A. Hashem (Теория и практика переработки мяса)
The purpose of this study was to evaluate the effect of replacing nitrite with ginger powder in brine on the quality of cured beef. Five kilograms of fresh beef from a mature White Fulani bull was purchased and used for this study. The excessive fat and connective tissues were trimmed off the meat, and the meat slab was chilled at 4°C for 24 hours before further processing. Nitrite, salt, dextrose and ginger powder were purchased, measured out to prepare brine solution of five concentration levels each level constituted a mode of treatment, where T0 served as control reference sample with nitrite, which nitrite was replaced with ginger power in the following concentrations: T1 = 10%, T2 = 15%, T3 = 20% and T4 = 25%. The beef was cured with brine injecting and immersing the samples into brine solution for 72 hours, and refrigerated at 4°C. The cured beef samples were taken out of the brine, rinsed, wrapped into foil paper and baked in the oven at 204°C for 20 mins and cooled to room temperature (27°C). Cured beef samples data were analysed with the help of analysis of variance (ANOVA) following the procedures of SAS (2002) with means significance determined at p < 0.05. There were significant differences (p < 0.05) in the physical properties, proximate analysis, vitamin and mineral contents, microbial loads and organoleptic characteristics of beef cured with ginger powder in brine, in T3 featuring the best-quality and highest (p < 0.05) overall acceptability. In conclusion, ginger powder used in this study as replacement of nitrite enhanced the overall quality of cured beef without detrimental consequences for the consumers, especially in T3 which concentration was therefore recommended.